2002
DOI: 10.1097/00000433-200206000-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Newspaper Surveillance Study of Homicide-Suicide in the United States

Abstract: The objective of this study was to identify the number and subtypes of homicide-suicides in the United States by age group and state over a 3-year period from 1997 through 1999. A total of 673 homicide-suicides, including 674 perpetrators and 779 victims, were identified from Internet searches of 191 national newspapers, and they were classified according to a modified Hanzlick-Koponen typology. One quarter of the homicide-suicides were perpetrated by persons 55 years or older, and 77% were spousal/consortial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(120 citation statements)
references
References 22 publications
4
113
1
2
Order By: Relevance
“…Furthermore, it was found that IPV was common in both groups-a finding reported by others cross-culturally (Lindqvist & Gustafsson, 1995;Malphurs & Cohen, 2002;Morton, Runyan, Moracco, & Butts, 1998;Palermo, 1994;Stack, 1997). Here, physical abuse is typically committed by a possessive male and arises out of suspected infidelity.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Furthermore, it was found that IPV was common in both groups-a finding reported by others cross-culturally (Lindqvist & Gustafsson, 1995;Malphurs & Cohen, 2002;Morton, Runyan, Moracco, & Butts, 1998;Palermo, 1994;Stack, 1997). Here, physical abuse is typically committed by a possessive male and arises out of suspected infidelity.…”
Section: Discussionmentioning
confidence: 70%
“…IPH also has the highest incidence of homicide-suicide of any type of homicide. In addition, IPH followed by a self-destructive act (SDA; for example, suicide or attempted suicide) is almost exclusively committed by men (Barber et al, 2008;Harper & Voigt, 2007;Koziol-McLain et al, 2006;Malphurs & Cohen, 2002;Marzuk, Tardiff, & Hirsch, 1992;Milroy, 1995;Roberts, 2009;Starzomski & Nussbaum, 2000). Men committing lethal SDAs leave little or nothing for scientists to learn about the antecedents of the event without resorting to secondary resources, such as psychological autopsy, for information (Cavanagh, Carson, Sharpe, & Lawrie, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…16 While males remain the most likely perpetrators in this age group, as many as 50% of male perpetrators identified in a study of homicide/suicide among the elderly identified the husband as the main caregiver in the relationship. 17 Recently, a comparison of homicide/suicide and suicides found that perpetrators of homicide/suicide over the age of 55 were more likely than those who died by suicide to have reported a recent illness, to have provided care for another, and to have a history of domestic violence.…”
mentioning
confidence: 99%
“…Hence the image of the sinister `Extra-familial' assailant i.e. committed by a non-family member or acquaintance, is far less common, and the totally unknown stranger is even rarer (D'Orban, 1990;Somander & Rammer, 1991;Waterhouse et al, 1994;Pritchard & Bagley, 2001;Malphurs & Cohen, 2002;Romain et al, 2003;Moskowitz et al, 2005).…”
Section: Wells In 2003mentioning
confidence: 99%